A Randomized, Open‐Label, Crossover Phase 1 Study to Evaluate the Effects of Food on the Pharmacokinetics of a Single Oral Dose of a 15‐mg Tylerdipine Tablet in Healthy Chinese Male Volunteers. Issue 1 (10th October 2018) - Wang, Lu; Xie, Lijun; Zhou, Sufeng; Wang, Yuanyuan; Chen, Juan; Zhou, Yanli; Liu, Yun; Zhang, Hongwen; Tao, Mingxue; Ou, Ning; Shao, Feng
Abstract: Tylerdipine hydrochloride is a novel L‐type and T‐type dual calcium channel antagonist that has the potential effects of expanding blood vessels and lowering blood pressure. It is expected to reduce the side effect of ankle edema observed with other drugs in the same class. A randomized, open‐label, crossover phase 1 study was performed to evaluate the effect of food on the bioavailability of tylerdipine. Fourteen healthy male volunteers were enrolled. The administration of tylerdipine after a high‐fat meal increased the bioavailability of tylerdipine. In the fed state there was a 130% increase in the mean total systemic exposure (AUCinf ) and a 73% increase in the mean peak plasma concentration (Cmax ) compared with that in the fasting state. The geometric mean ratios (90% confidence interval) of Cmax and AUCinf were 2.54 (1.94, 3.33) and 1.75 (1.50, 2.04) for tylerdipine. The exposures of the 2 main metabolites M2 and M4 were increased by approximately 10% after a high‐fat meal. The median time to peak plasma concentration of tylerdipine showed no difference between fasting and fed states.